Pengukuran Produktivitas dengan Analisis Manpower Terhadap Hasil Produksi pada Industri Ballpoint - Toyosito, Rakay Edhiargo; Ratoko, Sita Kurniaty; Wiyatno, Tri Ngudi (DPPM UNIVERSITAS PELITA BANGSA, 2021)
One measure of the extent to which resources are managed and used to optimize outcomes is the definition of productivity. In companies, manpower productivity measurements are conducted to analyze and improve production efficiency. This is also done to eliminate the root cause of labor productivity problems. This research is related to productivity analysis in the stationery (pen) production industry. A common problem is inefficiency and low productivity in the Company. Therefore, analyzing productivity related to efficiency, quality and effectiveness can help the Company in overcoming this problem. The result obtained in this industry is that the productivity value is good because there is no productivity value below 1. Moreover, productivity is also effective and efficient. Effectiveness is related to output, i.e. production output, as well as efficiency related to input (input), i.e. labor. Another factor is quality.